3b.) Use the division Algorithm. Let x be any integer ⇒ if x divided by 9, then remainders are 0, 1, 2, 3, 4, 5, 6, 7, 8 ⇒ 9k, 9k + 1, 9k + 2, 9k + 3, 9k + 4, 9k + 5, 9k + 6, 9k + 7, 9k + 8 To explain further: we have: x = 9q : x3 = (3q)3 x3 = 27q 3 x3 = 9(3q 3 ) x3 = 9q, where q = 3q 3 x = 9q + 1 = x3 = (9q + 1)3 x3 = 729q 3 + 1 x3 = 9(3q 3 ) + 1 x3 = 9q + 1, where q = 3q 3 , and x = 9q + 8 = x3 = (9q + 8)3 x3 = 729q 3 + 512 p √ x3 = 729q 3 + 512 x3 = 9q + 8, Since if satisfies the condition, ∴ The cube of any integers has one of the forms 9k + 1, or 9k + 8 ■ 3c.) Let x be any integer ⇒ if x divided by 4, the remainders are 0, 1, 2, 3, 4 1 ⇒ 5k, 5k + 1, 5k + 2, 5k + 3, 5k + 4 to prove further we have: x = 5q : x4 = (5q)4 x4 = 625q 4 x4 = 5(125q 4 ) x4 = 5q, whereq = 125q 4 , and x = 5q + 1 : x4 = (5q + 1)4 x4 = 625q 4 + 1 x4 = 5(125q 4 ) + 1 x4 = 5q + 1, whereq = 125q 4 Since it satisfies condition, ∴ The fourth power of any integers is either of the form 5k, or 5k + 1 ■ 4.) Using contradiction, we have to assume that 3a2 −1 is a perfect square Then 3a2 − 1 can be written as 3k or 3k + 1 ⇒ 3a2 − 1 = 3k or 3a2 − 1 = 3k + 1 ⇒ If 3a2 − 1 = 3k, then 3(a2 − k) = 1, since divide 1, then it is contradiction. ⇒ If 3a2 − 1 = 3k + 1, then 3(a2 − k) = 2, since not divide 2, then it is contradiction. Since, it does not satisfies the form of 3k and 3k = 1 ∴ 3a2 − 1 is never a perfect square. ■ 2 5.) Mathematical Induction: 12 , 22 , 32 + .... + n2 = n(n+1)(2n+1) 6 Proof: For n=1, the statement reduces to 12 1×2×3 6 and is obviously true. Assuming the statement is true for n = k: 12 + 22 + 32 +...+(k + 1)2 = (k+1)(k+2)(2k+3) 6 We will prove that the statement must be true for n = k+1: 12 + 22 + 32 +....+ (k + 1)2 = (k+1)(k+2)(2k+3) 6 To simplify if, we have (12 + 22 + 32 +...+(k + 1)2 = (k+1)(k+2)(2k+3) 6 = (k)(k+1)(2k+1) 6 = (k)(k+1)(2k+1)+6(k+1)2 6 = (k+1)[(k(2k+1)+6(k+1)] 6 = (k+1)(2k2 +7k+6) 6 = (k+1)(k+2)(2k+3) 6 + (k + 1)2 Since the left-hand side is equal to the right-hand side ∴ n(n+1)(2n+1) 6 is an integer for every n ≥ 1. ■ 6.) Using modular Arithmetic Let n= 7m for some integer remainder −3 ≤ r ≤ 3; We can have n=r (mod 7) Since (−x)3 = (−x)3 , we have to check or finite 3 list of remainders: 03 = 0 (mod7) 13 = 1 (mod 7) 23 = 8 (mod 7) 33 = 27 (mod 7) These clearly lie -1,0,1 ∴ The cube of any integer is of the form of 7k or 7k ± 1 ■ 8.) Proof: Let x be an integer. x=2n is the form of an even integer. Square this even integer. which is a multiple of 4. so, the number by the two right-most digit must be divisible by 4. Since, all given digits formed number 11, then it is not divisible by 4. Let x be an odd integer. x=2n+1 is the form of an odd integer. square this odd integer. Since, it is one more than a multiple of 4 then we have to subtract 1 from number form of two-right most digits. Performing this, we have 10 - which is not divisible by 4. Since it is does not satisifies x=2n and x=2n+1 ∴ no integer in the following sequence is a perfect square: II, III, 4 IIII, IIIII,... ■ 10.) Proof by Mathematical Induction Let n=1 1[7(12 ) + 5] = 7+5 = 12 Let n = m for some integer m ≥ 1 m(7m2 + 5) = 7m3 + 5m. ⇐= Let’s express as 6a. We have to assume that 7m3 + 5m is divisible by 6. Next, Let n= m+1 (m+1) (7(m + 1)2 + 5) (m+1) (7m2 + 14m + 7 + 5) (m+1) (7m2 + 14m + 12) 7m3 + 14m2 + 12m + 14m + 12 7m3 + 21m2 + 26m + 12 (7m3 + 5m) 21m2 + 21m + 12 6a +3 (7m2 + 7m4) When m is odd, 7m2 + 7m + 4 When m is even, 7m2 + 7m + 4 Since, 7m2 + 7m + 4 is always divisible by 2 Then 3(7m2 + 7m + 4) is divisible by 6. To explain further: We let 3(7m2 + 7m + 4) be equal to 6b 5 = 6a+6b = 6(a+b) ⇐= always divisible by 6 Since, it satisfies m and m+1, it’d be mean that it’ll work for 1,2,3,...+ z ∴ n (7n2 + 5) is the form of 6k for every n ≥ 1 (■ 11.) Let n = 2k + 1, K ∈ N Now, n4 + 4n2 + 11 = (2k + 1)2 + 4 (2k + 1)2 + 11 = (4k 2 + 4k + 1)2 + 4(4k 2 + 4k + 1) +11 = (16k 4 + 16k 2 + 1 + 32k 3 + 8k + 8k 2 ) + 16k 2 + 16k + 4 + 11 = 16k 4 + 32k 3 + 40k 2 + 24k + 16 = 16[k 4 + 2k 3 + 1]+ 40k 2 + 24k Since, = 16[k 4 + 2k 2 + 1]+ (80k2 +48k) 2 = 16[k 4 + 2k 2 + 1]+ 16k(5k+3) 2 k(5k+3) 2 is integer for all N of K so, we assume k(5k+3) =m 2 Now, n4 + 4n2 + 11 = 16[k 4 + 2k 2 + 1] +16m = 16[k 4 + 2k 2 + 1 + m], where k=k 4 + 2k 2 + 1 + m Since, 16 divides n4 + 4n2 + 11 ∴ n4 + 4n2 + 11 is the form of 16k for every odd Z ■ 4.) Assuming that gcd (a,b) = 1, Prove the ff: 6 a.) gcd (a+b, a-b) = 1 or 2 [Hint: let d = gcd (a + b, a − b) and shows that d|2a, d|2b, and thus that d ≤ gcd (2a,2b) =2 gcd (a,b) Proof: Let d|a + b, a-b, then d|(a + b) + (a − b)=2a, and d|(a + b) − (a − b) = 2b so, d|gcd (2a, 2b) = 2 Now, we assume that the greatest common divisor of a + b and a − b is d. This means, both a + b and a − b are divisible by d, i.e. d is a factor of a + b and a − b. Therefore, we can safely assume that a + b = p(d) and a − b = g(d). Where p and g are other factors of a + b and a − b respectively. Now, we will add p(d) and g(d) =⇒ 2a = p(d) + g(d) =⇒ 2a = d(p + q) From the above equation, We can say that d is a factor of 2q. Similarly, We will now subtract g(d) from p(d) =⇒ 2b = p(d) − g(d) =⇒ 2b = d(p − g) Thus, We can also say that d is a factor od 2b. Therefore, this is only posible if either d = 1or2 Hence, GCD (a + b, a − b) = 1 or 2. ■ b.) gcd (2a + b, a + 2b) = 1 or 3 7 Since, gcd (a, b) = 1, There exists integer x, y such that ax + by = 1 Proof: Suppose gcd (a,b) = 1 Let d = gcd (2a + b, a + 2b). Then d|(2a + b) and d|(a + 2b). d|2(2a + b) - (a + 2b) =⇒ d|3a d|2(a + 2b) - (2a + b) =⇒ d|3b then, d|3a =⇒ d|3ax d|3b =⇒ d|3by Hence, d|(3ax + 3by) =⇒ d|[3(ax + by)] =⇒ d|3[sinceax + by = 1] =⇒ d = 1 or d = 3.■ c.) gcd (a + b, a2 + b2 ) = 1 or 2 Proof: Suppose gcd (a, b) =1 Let d = (a + b, a2 + b2 ) I f d divides a + b then it divides a(a + b) = a2 + ab so if it also divides a + b2 , then it divides, 2 a2 + ab - (a2 + b2 ) = ab − b2 =b(a − b) 8 A similar calculation shows it divides a(a − b) Then from gcd (a, b) = 1, we get d divides a − b: then it divides (a + b) + (a − b) =2a and (a + b) + (a − b) = 2b, so d = 1 or d = 2 ■ d.) gcd (a +b, a2 − ab + b2 ) = 1or 3 Proof: Let d = a2 − ab + b2 Since d|(a + b) and d|(a2 − ab + b2 ) =⇒ d|[(a + b)2 − a2 − ab + b2 ] =⇒ d|3ab Therefore, d|[3b(a + b) − 3b], i.e, d|3b2 Similarly it can be shown that d|3a2 Therefore, d|(3a2 , 3b2 ) =⇒ d|3(a, b)2 =3 Hence, (a + b, a2 − ab + b2 ) = 1 or 3. ■ 5.) For n ≥ 1, and positive integers a,b, Show the following: a.) If gcd (a, b) = 1, then gcd (an , bn ) = 1 Proof: Suppose gcd (a, b) = 1 =⇒ gcd (a2 , b2 ) = 1 gcd (a,b) = 1 implies 9 ax + by = 1 a2 x2 = 1 − 2by + b2 y 2 (2y − by 2 )b = 1 − a2 x2 (2y − by 2 )2 b2 = 1 − a2 x2 + a4 x4 (2x2 − a2 x4 ) a2 + (2y − by 2 )2 b2 ∴ gcd (a2 , b2 ) =1 ■ b.) The relation an |bn implies that a|b. Proof by Mathematical Induction: Lets denote the set of all positive integers n for which an |bn =⇒ a|b. We observe that when n=1 , a|b =⇒ a|b. This mean that 1 ∈ S. Next, we suppose that K ∈ S so that ak |bk . We need to show that ak+1 |bk+1 =⇒ a|b. i.e, that k + 1 ∈ S.,..... To show this, we assume that ak+1 |bk+1 . Which is precisely the case for n = k + 1 putting k + 1 ∈ S whenever K ∈ S. According to the first principle of finite induction; S must be the set of all positive integers. ■ 9.) Prove that the greatest common divisor of two positive integers divides their least common multiple. Proof: Let gcd (a, b)=d, lcm (a, b) = m 10 Since d|a and d|b, also, a|m and b|m So, d|m, ( by transitivity of division) =⇒ a=nd or b=md for some integers m and n gcd (a, b) × lcm(a, b) = ab ab = =⇒ lcm (a,b) = gcd(a,b) (nd)(md) d = d(mn) =⇒ d|lcm(a, b) ∴ mn ∈ Z =⇒ gcd (a, b) | lcm(a, b) ■ 12. Find integers x, y, z Satisfying gcd (198, 288, 512) = 198x+288y +512z Proof: Let d = gcd(198, 288) 288 = 98 × 1 + 90 198 = 90 × 2 + 18 90 = 18 × 5 + 0 So, gcd (198, 288) = 18 18 = 198 − 2 × 90 =198 − 2(288 − 198) = 3 × 198 − 2 × 288 Now, gcd (198, 288, 512) = gcd (918, 512) 512 = 18 × 28 + 8 18 = 2 × 8 + 2 8 = 4 ×2 = 04 So, gcd (18, 512)=2 2 = 18 − 2 × 8 11 = 18 − 2[512 − (8)(28)] =57 × 18 − 2 × 512 = 57(3 × 198 − 2 × 288) −2 × 512 = 171 × 198 − 114 × 288 − 2 × 512 x = 171, y = −114, z = −2 ■ 12